Plant Colonization by Biocontrol Bacteria and Improved Plant Health: A Review - Roohallah Saberi Riseh; Fariba Fathi; Mozhgan Gholizadeh Vazvani; Mika Tapio Tarkka (Frontiers in Bioscience-Landmark)
The use of biological control agents is one of the best strategies available to combat the plant diseases in an ecofriendly manner. Biocontrol bacteria capable of providing beneficial effect in crop plant growth and health, have been developed for several decades. It highlights the need for a deeper understanding of the colonization mechanisms employed by biocontrol bacteria to enhance their efficacy in plant pathogen control. The present review deals with the in-depth understanding of steps involved in host colonization by biocontrol bacteria. The colonization process starts from the root zone, where biocontrol bacteria establish initial interactions with the plant’s root system. Moving beyond the roots, biocontrol bacteria migrate and colonize other plant organs, including stems, leaves, and even flowers. Also, the present review attempts to explore the mechanisms facilitating bacterial movement within the plant such as migrating through interconnected spaces such as vessels or in the apoplast, and applying quorum sensing or extracellular enzymes during colonization and what is needed to establish a long-term association within a plant. The impacts on microbial community dynamics, nutrient cycling, and overall plant health are discussed, emphasizing the intricate relationships between biocontrol bacteria and the plant’s microbiome and the benefits to the plant’s above-ground parts, the biocontrol 40 bacteria confer. By unraveling these mechanisms, researchers can develop targeted strategies for enhancing the colonization efficiency and overall effectiveness of biocontrol bacteria, leading to more sustainability and resilience.